UPAYA HUKUM PELAKSANAAN EKSEKUSI PEMBAGIAN HARTA BERSAMA (STUDI PUTUSAN NOMOR : 27/PDT.G/2014/PN.BTM) - Putri, Ayu Nabilla; Ibrahim, Ukas (LPPM Universitas Putera Batam, 2020)
Marriage is a legal relationship between a men and a women for a long term. Marriage between man and woman who aims to estabilish a family and have children for the next generation. After the divorce, the problem does not stop there, there are still more problems such as the sharing of shared assets during the marriage. The purpose of this study is to explain the factors that prevented the defendant from carrying out the sharing of assets in accordance with the Court Decision, and legal efforts so that the defendant carried out the Court's Decision. This research uses normative legal research. The results of this study are based on the Decision of the Supreme Court of the Republic of Indonesia Number: 27 / PDT.G / 2014 / PN.BTM. The Panel of Judges decided to reject the claim filed by the Plaintiff because the claim for the distribution of shared assets has not been proven by the Plaintiff that any property which is the right of the plaintiff, and also that the agreement was not made before the marriage took place, nor was it legalized by the Marriage Registrar in accordance with clause 47 KHI.